Synergy Between Plantation And Mining Sectors: A Case Study Of Pt Bumi Sawindo Permai - Taufan Trianggara Atmaja; Achmad Fajar Hendarman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study explores how strategic foresight can support organizational transformation at PT Bumi Sawindo Permai (PT BSP) to foster synergy between plantation and mining sectors. Findings show that applying foresight tools such as scenario planning, visioning, and backcasting has enabled PT BSP to anticipate future uncertainties and realign its organizational structure, workforce strategy, and long-term vision toward becoming a land integrator within the PTBA ecosystem. Key transformation initiatives include restructuring for operational efficiency, enhancing workforce capabilities through targeted training and rotation, cultivating cross-sector leadership, and building a cohesive organizational culture. To sustain this transformation, the study recommends robust performance governance and strategic diversification into land reclamation and biomass services. Furthermore, active engagement with government regulators and alignment with shareholders PTBA and Danantara is essential to strengthen PT BSP’s mandate and ensure coherence with national energy transition goals and long-term ESG commitments.